2020
DOI: 10.1097/jsm.0000000000000881
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Calcific Tendinopathy of the Achilles Tendon and Dysmetabolic Diseases: An Epidemiological Survey

Abstract: This study reports the incidence of insertional calcific tendinopathy (ICT) of the Achilles tendon in the general population and the percentage of symptomatic patients. The secondary aim is to ascertain whether ICT is associated with diabetes mellitus, thyroid disorders, obesity, and hypercholesterolemia. We hypothesized that metabolic diseases increase the risk of ICT of the Achilles tendon. Design: Prospective observational study (level III study). Setting: Orthopedic Outpatients Clinic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…3 Graduate School of Wuhan University of Science and Technology, Wuhan, Hubei Province, P. R. China. 4 The First Clinical Medical School Of Southern Medical University, Guangzhou, Guangdong Province, P. R. China.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Graduate School of Wuhan University of Science and Technology, Wuhan, Hubei Province, P. R. China. 4 The First Clinical Medical School Of Southern Medical University, Guangzhou, Guangdong Province, P. R. China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…The incidence of Achilles tendon pain is approximately 6% in the general population, and 24% of the people suffering from heel pain were diagnosed as insertional Achilles tendinopathy (IAT) [2,3]. The incidence of IAT increases with age and is significantly higher in patients with metabolic diseases (e.g., diabetes mellitus, hypercholesterolemia, and hypothyroidism) [4]. However, the exact etiology and pathogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…16,19 Although some studies have been conducted, k the association between dyslipidemia and AT or ATR is still inconclusive. Moreover, studies 3,13,21,22,29,33 vary greatly regarding which lipid profile was related to Achilles tendon disorders, although a positive association between dyslipidemia and AT or ATR has been reported. Gaida et al 13 reported that higher TG levels, lower HDL-C levels, and higher TG-to-HDL-C ratios were associated with midportion AT with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately determine the risk posed by dyslipidemia, it is necessary to adequately adjust for other confounding systemic factors. Most of the previous studies aimed at determining the impact of dyslipidemia on the risk of AT 2,3,13,17,29 or ATR 17,21,22,28,33 either had small cohorts or were case-control studies. Moreover, an association between body mass index (BMI) and dyslipidemia was not ascertained.…”
mentioning
confidence: 99%
“…Calcific tendinopathy treatment: 23.3% of chronic IAT had calcification, especially in elderly patients (odds ratio [OR] 1.05). 5 It had resulted from the degenerative process of the tendon, whereas calcific tendinitis of shoulder occurs from calcium deposit by inflammatory processes, which can be resolved. 6 In most studies about extracorporeal shockwave therapy (ESWT) in chronic IAT, the outcome measurements are pain relief and improvement of function.…”
mentioning
confidence: 99%